Effect of a food supplementation and psychosocial stimulation trial for severely malnourished children on the level of maternal depressive symptoms in Bangladesh - Nahar, Baitun; Hossain, Iqbal; D. Hamadani, Jena; T, Ahmed; Persson, Lena (© 2015 Blackwell Publishing Ltd, 2017)
This article was published in Child: Care, Health and Development [© 2015 Blackwell Publishing Ltd] and the definite version is available at: http://onlinelibrary.wiley.com/doi/10.1111/cch.12176/abstract